Mindfulness meditation intervention with male collegiate soccer players: Effect on stress and various aspects of life - Vidic, Z.; St. Martin, M.; Oxhandler, R. (The Sport Journal, 2018)
Collegiate athletes face a unique set of challenges in an environment that demands their best in the athletic, academic, and personal arenas of their lives. In recent years, the National Collegiate Athletic Association (NCAA) has increased its attention towards the enhancement of collegiate athletes` overall mental health with the goal of helping athletes cope more effectively on- and off-the court. One technique that has gained attention in the sport setting due to its all-around beneficial effects on health and well-being and athletic performance is the practice of mindfulness. This mixed-method study investigated the effects of a 6-session mindfulness meditation intervention on a United States NCAA Division III men`s soccer team`s (n=18; ages 18-22) stress levels and various aspects of their lives. Qualitative results revealed that athletes had overall positive perceptions of the mindfulness meditation intervention across various aspects of their lives in the form of: enhanced focus, increased calmness, improved awareness, and being more present-oriented. Quantitative results demonstrated overall decreases in stress over the course of intervention, however these findings did not reach statistical significance. Overall, the findings of this study suggest that mindfulness meditation training has the potential to be an effective approach to assisting athletes derive positive benefits on- and off-the court.